A influência de instituições e do arcabouço institucional na emissão de gases de efeito estufa - Tateishi, Henrique Ryosuke (2019)
This study investigated the effectiveness of the Kyoto Protocol (KP) in regards to the Greenhouse Gases (GHG) emissions reduction on the first and early second decades of 2000s. It has also taken into account the institutional, such as democracy and property rights levels and development impacts of a countries. Furthermore, it has proposed to analyze the economic performance of Gross Product Value output and the environmental performance concerning the GHG emissions employing a technical efficiency and an environment efficiency measures, respectively. Moreover, it has been proposed to verify the effect of institutional framework on these efficiencies. This study employed a difference in difference model to measure the KP effectiveness and a stochastic frontier analysis to estimate the economic and environmental performances. The results point out an overall low effectiveness of KP. Taking into account different groups of countries with similar characteristics of development or institutional quality, the effectiveness of KP was also low. Countries with low development, low urbanization area covered and high inequality tended to reduce its emissions considering the time difference. Countries with high property rights and democracy level tended to increase the emissions over time. The effect of KP ratification was positive (reduced emissions) for the countries with average institutional and development levels. However, the effect of ratification was negative on the extremes: lowest and highest institutional quality and development levels. The main driver of economic output was capital input and the level of economic output presented a higher share in GHG emissions than the non-renewable energy utilization. The overall economic performance was higher than overall environmental performance. The analysis of the impact of institutional framework on efficiencies suggests mixed results.